2011
DOI: 10.3139/105.110117
|View full text |Cite
|
Sign up to set email alerts
|

Economic surface hardening by spray cooling

Abstract: The objective of the current investigation is a cost analysis of spray cooling based on the assessment of a machine-hour schedule. Here, a gear toothed component is used as an example which is induction hardened by means of the simultaneous dual frequency method and compared with conventional polymer quenching. By using hardness measurements and light-microscope examinations, it is demonstrated that comparable results are obtained for the induction hardening by employing spray cooling and those by polymer quen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Through variation of the spray parameters, such as the water and air pressures, the heat transfer coefficients at workpiece's surface can be precisely adjusted over a wide range, which is typically between those achieved by gas and immersion quenching . A detailed study of the resulting heat transfer coefficients regarding the variation of spray parameters, the number of nozzles, and the overlapping of spray cones is given by Herbst et al By employing water–air spray cooling, the mechanical properties, such as tensile strength, can be improved, the distortion during quenching can be reduced, and the residual stress state can be adjusted. In previous investigations using conventionally formed gear wheels made from 42CrMo4 hardening and tempering steel, it could be demonstrated that compressive residual stresses can be induced in the loading‐relevant regions of the tooth's flanks …”
Section: Introductionmentioning
confidence: 99%
“…Through variation of the spray parameters, such as the water and air pressures, the heat transfer coefficients at workpiece's surface can be precisely adjusted over a wide range, which is typically between those achieved by gas and immersion quenching . A detailed study of the resulting heat transfer coefficients regarding the variation of spray parameters, the number of nozzles, and the overlapping of spray cones is given by Herbst et al By employing water–air spray cooling, the mechanical properties, such as tensile strength, can be improved, the distortion during quenching can be reduced, and the residual stress state can be adjusted. In previous investigations using conventionally formed gear wheels made from 42CrMo4 hardening and tempering steel, it could be demonstrated that compressive residual stresses can be induced in the loading‐relevant regions of the tooth's flanks …”
Section: Introductionmentioning
confidence: 99%